Biogenesis of the cyanobacterial photosystem II complex: involvement of selected accessory factors with emphasis on the novel Psb35 protein - Pascual Aznar, Guillem Miquel (Jihočeská univerzita, 2021)
In the last twenty years, intensive work has been devoted to elucidating the structure and function of a number of protein factors involved in the assembly and repair of Photosystem II (PSII). These proteins are not found in the crystal structure of the active PSII but transiently interact with one or more of the assembly/repair intermediates in order to facilitate the PSII assembly/repair or protect their components. The principal aim of this thesis consists in the description of a novel PSII assembly factor that we termed Psb35. Additionally, research on the previously identified Ycf48 and RubA assembly factors is also presented. Based on these results their structure and function are further clarified.
Biogenesis of the cyanobacterial photosystem II complex: involvement of selected accessory factors with emphasis on the novel Psb35 protein
Keywords: Genetics; Proteomics; cyanobacteria; photosystem II; photosynthesis; chlorophyll-binding proteins; assembly factor; Genetics; Proteomics; cyanobacteria; photosystem II; photosynthesis; chlorophyll-binding proteins; assembly factor